Evaluación del potencial de energía solar, en la Parroquia Belisario Quevedo del Cantón Latacunga, en función del consumo energético del Campus Gral. Guillermo Rodríguez Lara de la ESPE Extensión Latacunga, periodo 2012 - 2013. Análisis de prefactibilidad para su inclusión - Acuña Coello, Fausto Vinicio (2013)
In this research, Evaluation of Solar Power potential in Belisario Quevedo Parish, Latacunga Canton, depending on consumption energy at General Guillermo Rodriguez Lara Campus, ESPE Latacunga Extensión. An energy consumption campus is evaluated using an energy analyzer of power quality and installed on the classroom block for a week period. Consumption is checked by performing an inventory of loads, especially fixtures installed throughout the building. A bibliographic review was performed to establish a suitable methodology to design a photovoltaic solar system connected to the (SFCR) network based on the useful area of generation. The technical and economic feasibility in order to incorporate a photovoltaic solar power generation system SFCR type, the energy system campus in agreement with regulation 004/11 of CONELEC the Electrical System Act and the Constitution industry is analyzed. Finally, a design for generating solar energy system is proposed as an alternative power source that best suited to Campus facilities.